Analisis Faktor yang Memengaruhi Kebijakan Dividen pada Perusahaan Sektor Perbankan - Lolita, Sella; Mertha, Made (E-Jurnal Akuntansi; Vol 33 No 9 (2023)DO - 10.24843/EJA.2023.v33.i09.p02, 2023)
Dividends are distributed as a company policy. Dividends are given to shareholders for their investments. The aim of the research is to obtain empirical evidence regarding the influence of profitability, liquidity and leverage on dividend policy. Research location for banking companies listed on the Indonesia Stock Exchange for the 2019-2021 period with a total of 36 companies observed. The analysis technique used is multiple linear regression. The research results show that increasing profitability and leverage increases dividend payments. Liquidity has no influence on dividend payments because the company has strong capital. This research has limitations, namely that it only examines three variables in the banking sector. Keywords: Profitability; Liquidity; Leverage; Dividend Policy; Banking